En jämförande studie av miljöcertifiering och lågenergihuskoncept för lokalbyggnader - Lindberg, Frida (2013)
Our world is in need of change, to live up to the international and national environmental and climate ob- jectives. For change to happen, a steep decline in emissions of environmentally hazardous compounds is necessary, in the close future. But whose responsibility is it to prevent global climate change? The Swedish construction and real estate sector accounts for about 40 % of energy use in Sweden, therefore, the sector has a large and important responsibility of the national environmental management. This analyze builds on an initial literature review and further on a specific case study. A local building owned by a property company in Luleå, has been studied. The building of study can be described as a typical local building from the 1960’s and in need of an energy renovation. Six different certifications has been studied and an- alyzed and then applied to the local building in Luleå. The main purpose with the study is to identify and compare the environmental certification used to certify buildings in Sweden.The systems require different amounts of recourses and knowledge, EU Greenbuilding is a system that aims to focus on energy and determined to be fully available for use in the certification of the studied building. The Swedish program Miljöbyggnad is a system that requires more steps and work during the operating period but through extensive renovations, long-term planning and knowledge deemed it still possible to certify under Miljöbyggnad.LEED and BREEAM are two foreign systems that are not yet common in Sweden. There is a lack of knowledge and evidence of past reference objects. The certification of these systems need a specific Swedish adaptation produced and it is likely to be complicated and extensive.The concept of zero energy buildings is provided in Sweden and builds on a technology that give the results a very energy efficient house. These concepts are very difficult to apply to existing buildings from the 1960s through renovation. It is usually simpler, leaner and more economical to build new ...